The Relevance of Cultural and Media Studies to Theatre and Television in Bali - Mark Hobart (Jurnal Kajian Bali (Journal of Bali Studies), 2011)
AbstractA critical approach to Balinese society presents a starkly different picturefrom the representations that Balinese usually tell themselves, whichare largely myths to disguise a painful reality. Bali no longer belongsto Balinese but to international capital, a process of alienation by whichBalinese energetically commoditize their culture while claiming theopposite. Even the frames of reference for discussing what is happeningare inadequate because they predate the rise of contemporary consumercapitalism and the mass media. That is why critical media and culturalstudies, disciplines designed precisely to address such phenomena, arepotentially so relevant for Indonesian intellectuals.